Multiscale pore‐network representation of heterogeneous carbonate rocks. Issue 7 (16th July 2016) - Pak, Tannaz; Butler, Ian B.; Geiger, Sebastian; van Dijke, Marinus I.J.; Jiang, Zeyun; Surmas, Rodrigo
Abstract: A multiscale network integration approach introduced by Jiang et al . (2013) is used to generate a representative pore‐network for a carbonate rock with a pore size distribution across several orders of magnitude. We predict the macroscopic flow parameters of the rock utilising (i) 3‐D images captured by X‐ray computed microtomography and (ii) pore‐network flow simulations. To capture the multiscale pore size distribution of the rock, we imaged four different rock samples at different resolutions and integrated the data to produce a pore‐network model that combines information at several length‐scales that cannot be recovered from a single tomographic image. A workflow for selection of the number and length‐scale of the required input networks for the network integration process, as well as fine tuning the model parameters is presented. Mercury injection capillary‐pressure data were used to evaluate independently the multiscale networks. We explore single‐scale, two‐scale, and three‐scale network models and discuss their representativeness by comparing simulated capillary‐pressure versus saturation curves with laboratory measurements. We demonstrate that for carbonate rocks with wide pore size distributions, it may be required to integrate networks extracted from two or three discrete tomographic data sets in order to simulate macroscopic flow parameters. Key Points: This work investigates the multiscale porosity of a carbonate rock We compare simulated and laboratory measured capillary‐pressure curves A workflow to select number and length‐scales of multiscale networks is presented